INFORM2 NivEnt: the first trial of the INFORM2 biomarker driven phase I/II trial series : the combination of nivolumab and entinostat in children and adolescents with refractory high-risk malignancies - Tilburg, Cornelis M. van; Witt, Ruth; Heiss, Melanie; Pajtler, Kristian Wilfried; Plass, Christoph; Poschke, Isabel; Platten, Michael; Harting, Inga; Sedlaczek, Oliver; Freitag, Angelika; Meyrath, David; Taylor, Lenka A.; et al. (BMC cancer, 2020)
BackgroundPediatric patients with relapsed or refractory disease represent a population with a desperate medical need. The aim of the INFORM (INdividualized Therapy FOr Relapsed Malignancies in Childhood) program is to translate next generation molecular diagnostics into a biomarker driven treatment strategy. The program consists of two major foundations: the INFORM registry providing a molecular screening platform and the INFORM2 series of biomarker driven phase I/II trials. The INFORM2 NivEnt trial aims to determine the recommended phase 2 dose (RP2D) of the combination treatment of nivolumab and entinostat (phase I) and to evaluate activity and safety (phase II).MethodsThis is an exploratory non-randomized, open-label, multinational and multicenter seamless phase I/II trial in children and adolescents with relapsed / refractory or progressive high-risk solid tumors and CNS tumors. The phase I is divided in 2 age cohorts: 12-21years and 6-11years and follows a 3+3 design with two dose levels for entinostat (2mg/m(2) and 4mg/m(2) once per week) and fixed dose nivolumab (3mg/kg every 2weeks). Patients entering the trial on RP2D can seamlessly enter phase II which consists of a biomarker defined four group basket trial: high mutational load (group A), high PD-L1 mRNA expression (group B), focal MYC(N) amplification (group C), low mutational load and low PD-L1 mRNA expression and no MYC(N) amplification (group D). A Bayesian adaptive design will be used to early stop cohorts that fail to show evidence of activity. The maximum number of patients is 128.DiscussionThis trial intends to exploit the immune enhancing effects of entinostat on nivolumab using an innovative biomarker driven approach in order to maximize the chance of detecting signs of activity. It prevents exposure to unnecessary risks by applying the Bayesian adaptive design for early stopping for futility. The adaptive biomarker driven design provides an innovative approach accelerating drug development and reducing exposure to investigational treatments in these vulnerable children at the same time.Trial registrationClinicalTrials.gov, NCT03838042. Registered on 12 February 2019.
Gesehen am 10.06.2021